MOLECULAR CHARACTERIZATION, EXPRESSION PATTERNS AND METHYLATION ANALYSIS OF ATP-BINDING CASSETTE SUB-FAMILY G MEMBER 2 (ABCG2) IN BROILERS - J. Y. Xing; Y. J. Zhang; W. Q. Jing; W. L. Li; Y. M. Yu (Journal of Animal and Plant Sciences, 2019)
As a member of the ATP-binding cassette (ABC) transporter superfamily, ATP-binding cassette sub-family G member 2 (ABCG2) plays an important role in clinical drug resistance and maintenance of cellular folate homeostasis. In this work, our aim was to clone and characterize the chicken ABCG2 (cABCG2) gene, investigate its mRNA expression levels in different tissues and relationship between expression and methylation. Our results showed that the chicken cDNA was 2155 bp (Genbank Accession No: KU351683) with a 2106 bp open reading frame, which encoded 701 amino acids. The cABCG2 amino acid sequence showed 55.92%- 97.43% identity with other animal species. A phylogenetic tree revealed that cABCG2 had the closest relationships with chicken and turkey. qPCR analysis indicated the highest cABCG2 expression levels were detected in liver, whereas the lowest expression levels were found in spleen. In addition, the expression levels of cABCG2 in liver of offspring, not only 21 days old but also 42 days old chicken, were significantly upregulated by dietary folate deficiency group during laying eggs (P≤0.05). Bisulfite sequencing results revealed that no significant differences were observed between normal folate group and folate deficient group (P>0.05). These studies will be helpful for future research cABCG2precise function and structure.
Keywords: ABCG2; broilers; cloning; folate; methylation.